The Effect of Zeatin on In vitro Propagation of Chrysanthemum Shoots (Chrysanthemum morifolium Ramat) - Normasari, Rut; Tilaar, Wenny; Timban, Firginia Yulita Rilya (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Chrysanthemum is a plant that has a high aesthetic value in its flowers. Chrysanthemum production fluctuates from year to year. One of the factors that influence this is the availability of chrysanthemum seeds. For this reason, it is necessary to propagate chrysanthemum seeds through mass propagation. Zeatin, which is a cytokinin, has the function of promoting the growth of lateral shoots. The purpose of this study was to evaluate the effect of zeatin on the propagation of chrysanthemum shoots. The explants used in this study were explants of chrysanthemum shoots in vitro. Explants were cultured on Murashige and Skoog (MS) media with the addition of zeatin (0, 0.5, 1, 1.5, and 2 ppm) for six weeks. The application of zeatin affected the number of shoots and leaves but did not affect plant height and wet weight. The number of shoots decreased with increasing zeatin concentration. The number of leaves per plant and wet weight increased at 0.5 ppm zeatin concentration and gradually decreased. Plant height increased with increasing zeatin concentration except at one ppm zeatin concentration which decreased. The highest chrysanthemum shoot propagation was produced on MS medium added with 0.5 ppm zeatin. Keywords : Zeatin, in vitro, mass propagation, chrysanthemum